Donne e sport in un (lungo) processo di affermazione ed emancipazione: Cantarella, E., & Miraglia, E. (2021). Le protagoniste. L’emancipazione femminile attraverso lo sport. Milano: Feltrinelli. - Castellano, Simona (Eracle. Journal of Sport and Social Sciences, 2022)
Although female athletes often must undergo a process of comparison with their male colleagues, with perceptible concrete differences concerning issues such as professionalism, ancient civilisations show how the practice of sport, even competitive sport, did not characterise exclusively male people: the sports practised by women – from different backgrounds – since ancient times are various. This element, together with stories of women who have distinguished themselves for sports merits in modern and contemporary society, contributes to defining the story of years and years of struggle against social and cultural prejudices, in a process of long emancipation, which has embraced different fields. “Le protagoniste. L’emancipazione femminile attraverso lo sport” by Eva Cantarella and Ettore Miraglia reflects precisely on these aspects, starting with Greek civilization and presenting various photographs of women who, by distinguishing themselves in various sporting disciplines, have contributed to defining women's emancipation in multiple fields.